2022
DOI: 10.3389/fpain.2022.836705
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Exposure in Preterm Infants: Five-Year Neurodevelopmental and Socioemotional Assessment

Abstract: ObjectiveTo evaluate the association between cumulative fentanyl dose during neonatal intensive care and 5-year neurodevelopmental and socioemotional outcomes in very preterm infants.Materials and MethodsPatient demographics and clinical factors during the perinatal and neonatal course were collected in 84 patients born between 23- and 30-weeks gestational age (GA). Cumulative fentanyl dose during neonatal intensive care was calculated. Developmental testing at age 5 years included the Wechsler Preschool and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(72 reference statements)
0
2
1
Order By: Relevance
“…Thus no definite conclusion could be reached concerning the potential effect of opioids, in general, or fentanyl per se, on blood pressure in preterm and term infants [90,103]. A longterm study of infants treated with fentanyl early after birth did not find any significant correlation between cumulative fentanyl exposure and neurodevelopmental outcomes at five years of age [107]. These results were consisted with previous reports in VLBWI at the age of two years [108].…”
Section: Fentanylcontrasting
confidence: 55%
“…Thus no definite conclusion could be reached concerning the potential effect of opioids, in general, or fentanyl per se, on blood pressure in preterm and term infants [90,103]. A longterm study of infants treated with fentanyl early after birth did not find any significant correlation between cumulative fentanyl exposure and neurodevelopmental outcomes at five years of age [107]. These results were consisted with previous reports in VLBWI at the age of two years [108].…”
Section: Fentanylcontrasting
confidence: 55%
“…The first report of a cohort of very preterm neonates (23-30 gestational age) evaluated the association between cumulative neonatal exposure to fentanyl by neurodevelopmental and socioemotional outcomes in children at 5 years of age. However, according to the authors, the conclusions of this study were still ambiguous [38]. Dosing: analgesia [39], intermittent slow IV push 0.0005-0.003 mg/kg/dose, continuous infusion 0.0005-0.002 mg/kg/hour; sedation, slow IV push 0.001-0.004 mg/kg/dose may be repeated every 2-4 hours, continuous analgesia/sedation initial 0.001-0.002 mg/kg then 0.0005-0.001 mg/kg/hour.…”
Section: Fentanylmentioning
confidence: 75%
“…Some studies have recently demonstrated adverse long-tern neurodevelopmental effects [ 32 ] whereas others demonstrated that low dose infusion did not affect [ 18 , 33 ]. These long-term effect do not occur with fentanyl [ 34 ]. Regarding mechanical ventilation, it is preferable not to do it routinely, but only in selected patients [ 18 ].…”
Section: Management Of Painmentioning
confidence: 99%